Cervical Vertebrae Column Radiography with Suspective Fractures of the Corpus and Processus Spinosus Cervicalis at Columbia Asia Hospital Medan - Sihotang, Sri Nanda; Sidauruk, Juliana (International Journal of Public Health Excellence (IJPHE), 2023)
Veterbra Cervicalis is a spine consisting of seven segments which have small segment bodies and large segment openings. The function of the Veterbra Cervicalis is to cover and protect the spinal nerves, which act as support for almost two-thirds of the body's weight. As for the purpose of the work write scientific This in arrange is for show fracture and abnormality on the organ being examined, to obtain image criteria that can be appropriate to the case, for know location fracture the, for straighten up diagnosis in accordance with the case. Aircraft X-ray is Wrong One equipment installation radiology which has an important role in producing X-rays and providing images of objects on X-ray film. Radiographic techniques to show the anatomy of the Cervical Vertebral Column and its abnormalities, including cervical fractures, can theoretically be done with several projections, namely AP (Antero - Posterior), Lateral, Hyperextension and Hyperflexion. After carrying out a radiographic examination of the Cervical Vertebra Column with a suspected fracture in the Anterior part of the Cervical Vertebrae Corpus -5 and Cervical Spinous Process -2 at Columbia Asia Hospital Medan, the author concluded that the projections used were Anterior Posterior (AP) and Lateral projections. In the AP projection carried out at Columbia Asia Hospital Medan, a fracture appeared in the anterior portion of the Cervical Corpus -5, and in the lateral projection, a fracture appeared in the spinous process. Cervical -2.